2022
DOI: 10.3389/fgene.2022.972043
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and prognostic value of m5C regulatory genes in hepatocellular carcinoma

Abstract: Background: A high mortality rate makes hepatocellular carcinoma (HCC) one of the most common types of cancer globally. 5-methylcytosine (m5C) is an epigenetic modification that contributes to the prognosis of several cancers, but its relevance to HCC remains unknown. We sought to determine if the m5C-related regulators had any diagnostic or prognostic value in HCC.Methods: M5C regulatory genes were screened and compared between HCC and normal tissue from The Cancer Genome Atlas (TCGA)and Gene Expression Omnib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…The clinical usefulness of this study was validated in patients with HCC, indicating that this predictive pattern possesses significant diagnostic worth for 1-year, 3-year, and 5-year survival rates, the AUC values in the training cohort were 0.773, 0.699, 0.677. Models constructed based on m 6 A, m 7 G or m 5 C-related regulatory genes for the diagnosis in patients with HCC has been reported, the AUC values range from 0.61 to 0.74 [ 38 40 ]. However, so far, except for AFP, there is no single stand-alone biological indicator that has yet been identified as a biomarker for the diagnosis of HCC [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical usefulness of this study was validated in patients with HCC, indicating that this predictive pattern possesses significant diagnostic worth for 1-year, 3-year, and 5-year survival rates, the AUC values in the training cohort were 0.773, 0.699, 0.677. Models constructed based on m 6 A, m 7 G or m 5 C-related regulatory genes for the diagnosis in patients with HCC has been reported, the AUC values range from 0.61 to 0.74 [ 38 40 ]. However, so far, except for AFP, there is no single stand-alone biological indicator that has yet been identified as a biomarker for the diagnosis of HCC [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of data have introduced m5C modification as an important regulator in post-transcription. In the study of carcinogenesis, m5C-modified genes have been reported to be associated with a variety of cancers, including bladder cancer ( 19 ), hepatocellular carcinoma ( 20 ), glioblastoma multiforme ( 21 ), and leukemia ( 22 ). However, limited pieces of evidence have focused on the function of polymorphisms of m5C genes on disease susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there are an increasing number of studies working on the prognostic model of HCC based on ferroptosis phenotypes ( 37 ), cuproptosis-related genes ( 38 ), m 5 C regulatory genes ( 39 ), hypoxia-related angiogenic genes ( 40 ), et al. They all showed meaningful clinical implications to some extent.…”
Section: Discussionmentioning
confidence: 99%